United in Prevention–Electrocardiographic Screening for Chronic Obstructive Pulmonary Disease - Lazovic, Biljana (AVICENA, d.o.o., Sarajevo, 2013)
CONFLICT OF INTEREST: NONE DECLARED INTRODUCTION: P-wave abnormalities on the resting electrocardiogram have been associated with cardiovascular or pulmonary disease. So far, “Gothic” P wave and verticalization of the frontal plane axis is related to lung disease, particularly obstructive lung disease. AIM: We tested if inverted P wave in AVl as a lone criteria of P wave axis >70° could be screening tool for emphysema. MATERIAL AND METHOD: 1095 routine electrocardiograms (ECGs) were reviewed which yielded 478 (82,1%) ECGs with vertical P-axis in sinus rhythm. Charts were reviewed for the diagnosis of COPD and emphysema based on medical history and pulmonary function tests. CONCLUSION: Electrocardiogram is very effective screening tool not only in cardiovascular field but in chronic obstructive pulmonary disease. The verticality of the P axis is usually immediately apparent, making electrocardiogram rapid screening test for emphysema.